Bhutan Development Update, April 2014 - World Bank (Washington, DC, 2014)
After a policy-engineered slowdown in 2012, which saw GDP growth decline to 4.8 percent, the lowest since 2008, Bhutan's economy is expected to rebound to 6.5 percent this year, supported by hydropower construction and higher electricity and food production, following favorable rains. The tight fiscal stance introduced in 2012 has been maintained to bring spending in line with lower non-hydro revenues and a slowdown in foreign grant disbursements, but the revenue situation is expected to improve with the commissioning of cement and electricity projects. Bhutan's external debt, at 85 percent of GDP, remains high, but is likely to fall sharply as assured hydropower revenues begin to flow from projects for which the external loans were taken. However, its narrow exports base and the large rupee-reserves mismatch make the country vulnerable to shortfalls in external earnings and pose a moderate risk. Bhutan's success in reducing absolute poverty is noteworthy, with the poverty rate falling from 23 percent in 2007 to 12-13 percent in 2012, improving the lot of the poorest segments of the population rather than merely that of those clustered around the poverty line. A rapid growth of commercial agriculture, expanding rural infrastructure, and beneficial effects from the construction of massive hydropower projects has established a sound platform for further poverty reduction. However, continued out-migration to urban areas and vulnerability of infra-marginal groups, the relative absence of formal social protection institutions, youth unemployment, and the persistence of malnutrition, anemia and stunting point to the need for continued effort at tackling non-income poverty. The macroeconomic projections for 2014 set GDP growth at 7.3 percent, stemming from new projects, increased tourism receipts, easier credit conditions and the effects of the Economic Stimulus Plan.